Pelaksanaan Penyidikan Tindak Pidana Pembukaan Lahan Perkebunan Di Hutan Lindung Berdasarkan Undang-Undang Nomor 18 Tahun 2013 Tentang Pencegahan Dan PemberantasanPerusakan Hutan Di Kabupaten Siak - Kurniawan, Jumarhadi; ', Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Forest as a profit of international development have a real benefit for the life ofIndonesia, as benefit ecology, cultural social as well as economy, in equal and dynamic. Thatis why forest must be administered, managed, protected and used sustainable for prosperity ofhuman being. Forest destruction as referred to constitution involved illegal logging and/orforest use unauthorized which is organized. Organized forest destruction is activitiesperformed by structured group, which consisting of 2 (two) or more, and which is acttogether at a certain time with intention of forest destruction.The problem in this research is 1) How the investigation of agricultural expansioncrime in protected forest under the law Number 18 by 2013 about prevention and combatingforest destruction at Siak District? 2) What is the problems in investigation of agriculturalexpansion crime in protected forest under the law Number 18 by 2013 about prevention andcombating forest destruction at Siak District? 3) How the effort made to overcoming theproblems of the investigation of agricultural expansion crime in protected forest under thelaw Number 18 by 2013 about prevention and combating forest destruction at Siak District?The research method in this research is sociological. The location of this research is done inthe Police Office of Mandau River of Siak District. The population in this study is The Headof Forestry Office Siak District, The Head of Forest Protection and Security of Siak District,The Policement of Mandau River of Siak District, destructive community forest preserve.The data source nature of this study are primary and secondary data sources with datacollection techniques such as interviews, review of the literature. The data obtained will beanalyzed using qualitative methods.Overview common in this study is an overview of a crime, an overview of theinvestigation and an overview of agricultural expansion crime . An overview of the crime ofdiscussing the notion of crime, the elements of a criminal offense . An overview of theinvestigation to discuss the duties and authority of the investigator, efforts in theinvestigation. An overview of agricultural expansion crime discuss the notion of agriculturalexpansion crime, agricultural expansion crime provisions , criminal and conviction of thecrime of agricultural expansion. Investigation of agricultural expansion crime at protectedforest Under the law Number 18 by 2013 about prevention and combating forest destructionat Siak District, there are some obstacles one of them is the lack of coordination betweenrelevant agencies, so that they still lack the reach of the investigating authorities to conductan investigation into the location. In terms of transportation also remains inadequate, makingit difficult to supervise the protected forest itself. Attempts by the investigator to overcomethe problem is the preventive and repressive efforts. Where preventive measures over thetreatment or prevention alone, while the repression has entered into a direct action against theperpetrators of criminal acts in the protected forest clearing.Keywords : Investigation - Crime – Agricultural - Forest